1999
DOI: 10.1080/00365529950172880
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Significance of Slightly to Moderately Increased Liver Transaminase Values in Asymptomatic Patients

Abstract: Most transaminitis patients had steatosis, and some had defined diseases including chronic hepatitis C. Chronic hepatitis of unknown etiology was found in a substantial proportion (24%) of a population living in an area with a low burden of hepatic viruses and genetic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…There is of course a possibility that the frequency of NAFLD could be higher if patients had been biopsied. In a previous study by Mathiesen et al, it was also conducted in Sweden the prevalence of steatosis was 40% among subjects who underwent liver biopsy due to asymptomatic slightly-moderately elevated LFTs of all causes [25]. More newer sensitive non-invasive techniques like magnetic resonance spectroscopy have come to clinical usage after this study is designed, which could strengthen the results it had been used.…”
Section: Discussionmentioning
confidence: 82%
“…There is of course a possibility that the frequency of NAFLD could be higher if patients had been biopsied. In a previous study by Mathiesen et al, it was also conducted in Sweden the prevalence of steatosis was 40% among subjects who underwent liver biopsy due to asymptomatic slightly-moderately elevated LFTs of all causes [25]. More newer sensitive non-invasive techniques like magnetic resonance spectroscopy have come to clinical usage after this study is designed, which could strengthen the results it had been used.…”
Section: Discussionmentioning
confidence: 82%
“…However, this normal range was calculated from a supposedly healthy reference population, which probably included people with mild to moderate chronic liver disease. Several previous studies have demonstrated that serum aminotransferase level, even within the normal range, may be associated with morbidity and mortality 15-17,22,29,47. The progressive linear association between serum aminotransferase level and the metabolic syndrome suggests that people with high normal aminotransferase levels may need further investigation for the presence of fatty liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…These definitions did not consider that metabolic covariates caused liver injury with slight-to-moderate ALT elevation 3, 106. Because of the increasing prevalence of patients with metabolic disorders, the clinical significance of ALT values have been recognized.…”
Section: Several Concerns That Clinicians Should Raisementioning
confidence: 99%